Between Meaning-Making and Learning the “Rule”: The Case of a Prospective Teacher of Mathematics at the Secondary Level - Proulx, Jérôme (Alberta Journal of Educational Research, 2008)
This article reports on a case study intended to improve understanding of the development and characteristics of prospective mathematics teachers’ oral explanations. The teaching practices of Donna, who taught algebraic operations, were analyzed, after which she was interviewed. The presence of an important tension in how Donna explained mathematics emerged where her explanations were divided between contextualized understandings and formalized knowledge, highlighting the difficulties in teaching of transition from one to the other. The article concludes with a discussion of a plausible rationale for this tension, which emerges from an understanding of mathematics as reduced to a call for formalized procedures.